Internet Use in a Central African Country: An Evidence of Cameroon (Global Journal of Human-Social Science, 2022)
The objective of this study is to identify the different activities that motivate individuals to use the Internet in Cameroon. Specifically, this is to show that activities related to the search for information online, academic activities online, activities on digital social media, listening and downloading music online, online watching and movie download, online purchases and sales, online administrative services and online sports activities motivate the use of the Internet by individuals in Cameroon. The methodology implemented uses data from the survey of the practice of new digital media in Cameroon (PRANOME) carried out in 2021 in the cities of Yaoundé, Douala, Mfou, and Soa under the supervision of the Center of Research in Economic and Management (CEREG) of the University of Yaoundé 2-Soa in Cameroon. The results of the estimates made on the basis of the binary Logit model show that Internet use has a positive and significant effect at the 1% level on the activities of listening and downloading online music, watching and for downloading movies online; searching for information online and on digital social media.
Keywords: internet; use; individuals; activities; logit